Kalimat Majemuk pada Berita “Darurat Militer Jadi Bumerang, Presiden Korsel Terancam Hukuman Mati” dalam Unggahan CNBC Indonesia - Kharismawan, Divan Gilbran (EDU-KATA, 2025)
This research aims to analyze the structure of compound sentences in digital news articles related to political events of the President of South Korea, Yoon Suk Yeol, published on CNBC Indonesia. The main focus of the research is to identify the types of compound sentences used in news reports, with an emphasis on analyzing compound sentences using the theory of compound sentence syntax. This research uses a qualitative descriptive approach with data collection techniques through literature study and document analysis. The data used comes from sentences in the news that discuss current political issues related to President Yoon, such as martial law and impeachment. In this analysis, special attention is paid to sentences that use subordinate clauses, conjunctions, and compound sentence structures that describe cause-and-effect relationships, time, and political context. This concept of compound sentences is used to understand the relationship between clauses in the reported political context. The research results show that multilevel and mixed compound sentences have an important role in conveying complex and layered information, which is often needed in news reports about political events. In addition, the subordinate clauses in these sentences help clarify the relationship between events and their impact on society and government. Through this analysis, it can be understood how sentence structures in digital news support readers' understanding of ongoing political events, as well as exploring the language techniques used to strengthen messages in news reports.